Visualisasi dan Analisis Distribusi Kasus Kusta di Jawa Barat Tahun 2016–2024 Menggunakan Power BI - Zahra, Vania Ardelia; Voutama, Apriade (LPPM Universitas Sains dan Teknologi Komputer, 2026)
Leprosy remains a significant public health concern in Indonesia. West Java Province, as one of the most populous regions, continues to report new leprosy cases annually. Understanding the distribution of these cases is crucial for disease monitoring and early identification of affected areas. This study aims to visualize the distribution of new leprosy cases in a dashboard by districts and cities in West Java during 2016–2024. Secondary data were obtained from the Portal Data Jawa Barat, which provides the number of new cases per district and city. The study employs descriptive analysis with a dashboard-based data visualization approach. The dashboard presents comparisons of case numbers, yearly trends, and the proportional contribution of each district/city in an interactive, easy-to-understand format. Results show that new leprosy cases vary across districts and cities and fluctuate over the observed period. Some regions consistently report higher case counts, resulting in differences in their contributions to the provincial total. The dashboard facilitates rapid monitoring of case distribution and provides stakeholders with a clear visual overview of leprosy in West Java. This study provides comprehensive visual information on leprosy distribution, supporting stakeholders in planning effective public health strategies